Technocracy Revisited: the Polish Security Dispositif and Ukrainian Migration to Poland - Marta Jaroszewicz; Jan Grzymski (Journal of Contemporary European Research, 2021)
The article investigates the reaction of the Polish technocratic security dispositif to the arrival of Ukrainian migrants in Poland between 2014-2020. It contributes to the studies on securitisation and on technocracy by proposing to re-conceptualise research on the security practices towards migration, drawing upon the notions of a security dispositif and regime of practices. It is exemplified by migration from Ukraine to Poland. The paper distinguishes three regimes of practices within Polish migration control: state ignorance, technocratic governance and neighbourhood. Contrary to most securitisation practices on migration to the European Union from the South, there have been very few populist ‘speech acts’ by Polish political agents that would have positioned the migration from Ukraine as an existential threat. The article concludes that the Polish security dispositif mainly mobilised state ignorance as a resource in governing migration, since neither new legal nor institutional practices were adopted to address the increased arrivals of Ukrainians. Simultaneously, this was accompanied by an internal logic of technocratic governance and its ubiquitous strategic tendency to widen surveillance and control capacities towards foreigners. The article also highlights the role of local identity and the politics of memory in governing Ukrainian migration to Poland.